1978
DOI: 10.4269/ajtmh.1978.27.508
|View full text |Cite
|
Sign up to set email alerts
|

Serological Diagnosis of Bancroftian and Malayan Filariasis *

Abstract: A study was undertaken to define the sensitivity and specificity of serological tests in bancroftian and malayan filariasis and correlate the findings with clinical disease. Sera were collected from subjects on three different islands in the Philippines: one endemic for bancroftian filariasis, another endemic for malayan filariasis and the third without endemic filariasis. Antibodies were measured, using Brugiamalayi as the source of antigen. Antibodies against adult worms measured by indirect immunofluorescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

1979
1979
2009
2009

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 9 publications
1
10
0
Order By: Relevance
“…Similar results were obtained by Rocha et al (1996), Nicolas et al (1997) and Itoh et al (1999). We also agree with Grove and Davis (1978), who suggest that the detection of microfilarial antibodies depends upon the relative release of MF into the bloodstream and the production of antibodies against those MF. Medeiros et al (1999) showed that men between 20-30 years of age are more susceptible to LF than are women of the same age group.…”
Section: Discussionsupporting
confidence: 92%
“…Similar results were obtained by Rocha et al (1996), Nicolas et al (1997) and Itoh et al (1999). We also agree with Grove and Davis (1978), who suggest that the detection of microfilarial antibodies depends upon the relative release of MF into the bloodstream and the production of antibodies against those MF. Medeiros et al (1999) showed that men between 20-30 years of age are more susceptible to LF than are women of the same age group.…”
Section: Discussionsupporting
confidence: 92%
“…Conceivably this extract could have been contaminated with antigens from microfilariae present in gravid females. On the other hand, the immediate hypersensitivity skin reactions observed by Grove et al reflect the presence of humoral, antibody-mediated immunity, whereas the lymphocyte transformation assay used in our studies is an in vitro correlate of cellular immunity (17)(18)(19). It is not unreasonable to assume that the crude saline extracts used in both studies contained several antigenic materials that might preferentially elicit humoral or cell-mediated reactions.…”
Section: Resultsmentioning
confidence: 93%
“…All 11 patients with elephantiasis reacted in vitro to this antigen, but none of 21 asymptomatic, and none of 21 patients with other stages of filariasis reacted to adult worm antigen. Such clear differences in the reactivity of individual patients to microfilarial and adult worm extracts were not noted by Grove et al (3,17), who studied the clinical usefulness of similarly prepared antigenic extracts for immunodiagnostic purposes by skin testing and measured serum antibody levels to microfilariae and adult worms. The reasons for this apparent discrepancy are not clear.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Studies by McGreevy et al (1980) and Piessens et al (1980) in Brugia malayi infections of man have highlighted the association between cellular and humoral responses to microfilarial antigens and amicrofilaremia. In several other systems, the appearance of antibodies to surface (sheath or cuticular) antigens of microfiliaria (mf) has been shown to correlate with suppression of microfilaremia (Wong 1964, Ponnudurai et al 1974, other literature cited in Grove & Davis 1978, Ambroise-Thomas 1979, Forsyth et al 1981a). Much attention is therefore focused on the surface of filariae and other nematodes as a site of antigens which may be targets of host-protective immunities (e.g.…”
Section: Onchocerca Gibsoni In Cattlementioning
confidence: 99%